Early Maladaptive Schemas and Internet Addiction: A Systematic Review - Sedighi, Masoud; Bekhradi, Reza; Ghaderi, Amir (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Internet addiction (IA) and its subtypes such as problematic use of social media, online gaming addiction, online pornography addiction, and smartphone addiction are increasingly recognized as behavioral disorders with significant psychosocial consequences. Early maladaptive schemas (EMSs), pervasive cognitive and emotional patterns formed in childhood, are thought to be the basis of vulnerability to these addictions. This review was conducted to systematically investigate the relationship between EMSs and various types of IA according to the PRISMA guidelines. Methods: A comprehensive literature search was conducted using Scopus, Web of Science, and PubMed. The inclusion criteria were peer-reviewed quantitative and meta-analyzed studies in English that examined EMSs and any form of IA. Data extraction and study selection were performed according to the PRISMA standards. Results: Nine studies met the inclusion criteria including cross-sectional (6 studies), causal- comparative (one study), review (one study) and meta-analytic (one study) designs, covering general IA, problematic use of social media, online gaming addiction, online pornography addiction, and smartphone addiction. Disconnection/rejection, impaired autonomy/performance, and impaired limits were the most consistently implicated EMS domains in the study. Conclusion: EMSs are strongly associated with multiple forms of IA. Schema-focused interventions may be beneficial for prevention and treatment.